Giant adrenal myelolipoma, a rare urological issue with increasing incidence: a case report - Tyritzis, Stavros I (Cases Network Ltd, 2009)
INTRODUCTION: Adrenal myelolipomas are relatively rare, non-functioning benign tumours composed of mature fatty and active hematopoietic elements. They can be asymptomatic, even if their size is massive. Diagnosis is relatively simple using ultrasound, computed tomography and magnetic resonance imaging. Surgical resection through an extraperitoneal approach is advocated in cases of symptomatic or large myelolipomas exceeding 5-cm in diameter. Their low incidence seems to be increasing from 0.2% to 10% during the last decade. CASE PRESENTATION: We present a case of a giant adrenal myelolipoma in a 68-year-old Caucasian male, who was presented with left lumbar pain. Renal ultrasound, CT and MRI demonstrated a well demarcated mass, with a maximum diameter of 10-cm. The differential diagnosis comprised the adrenal myelolipoma, the retroperitoneal liposarcoma and the renal angiomyolipoma. Thus, the patient was subjected to a left adrenalectomy. CONCLUSION: Multiple theories have been proposed for the increasing frequency and natural course of the adrenal myelolipoma, with chronic adrenal stimulation and the contemporary stressful lifestyle to be the most appealing. Surgical treatment is advocated through an extraperitoneal approach because of the quicker recovery of the patient and the smaller postoperative complication rate.